Philipp Niewöhner (ed.). The archaeology of Byzantine Anatolia. From the end of late antiquity until the coming of the Turks. - Intagliata , Emanuele E. (Journal of Greek Archaeology, 2019)
Until not long ago, the history and archaeology of Anatolia had traditionally been dominated by Roman-oriented studies. The surge of interest in Byzantine remains of the last decades has contributed considerably in shedding light on later phases, clarifying the development of important processes that had so far been understudied, like the evolution of urbanism. Invaluable review-like studies and groundbreaking discoveries such as those at Amorium, have helped re-draw a picture of Byzantine Anatolia that is not merely one of decline, collapse and urban shrinkage. All this has translated into a large corpus of secondary literature that is difficult to navigate by non-specialists that approach the topic for the first time.